2006
DOI: 10.1029/2005jd006439
|View full text |Cite
|
Sign up to set email alerts
|

Ozone profiles in the high‐latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)‐II: Comparison with other satellite sensors and ozonesondes

Abstract: A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 34 publications
7
35
1
Order By: Relevance
“…16) was also found around 40 km. Such a result was reported by Sugita et al (2006), in which the data around 40 km revealed a negative bias of ≈0.6 ppmv compared to some satellite occultation measurements. An inclusion of transmittance correction method developed for the satellite sunrise measurement mode into the ILAS-II V2 retrieval algorithm successfully improved the ILAS-II V2 data of those species.…”
Section: Tracer Correlation and Time Seriessupporting
confidence: 67%
See 3 more Smart Citations
“…16) was also found around 40 km. Such a result was reported by Sugita et al (2006), in which the data around 40 km revealed a negative bias of ≈0.6 ppmv compared to some satellite occultation measurements. An inclusion of transmittance correction method developed for the satellite sunrise measurement mode into the ILAS-II V2 retrieval algorithm successfully improved the ILAS-II V2 data of those species.…”
Section: Tracer Correlation and Time Seriessupporting
confidence: 67%
“…The ILAS-II V1.4 SH data did not reveal any degraded profiles as was found for the NH data Sugita et al, 2006). Since the transmittance correction was not applied to the satellite sunset mode, the differences in VMR between the two algorithm versions were due to the new tangent height registration and the trend correction method for the 100% signal part data (see Appendix A).…”
Section: Southern Hemispherementioning
confidence: 96%
See 2 more Smart Citations
“…Version 5.20 ILAS and version 1.4 ILAS-II ozone profiles were validated by comparing with various data sources (Sugita et al, 2002(Sugita et al, , 2006. These validations showed that ILAS ozone data agreed with other data sets within ±10 % with a few exceptions between 11 and 64 km (Table 1a, b).…”
Section: Ilas and Ilas-iimentioning
confidence: 84%